ANALISIS PENYEBAB GANGGUAN JARINGAN PADA DISTRIBUSI LISTRIK MENGGUNAKAN METODE FAULT TREE ANALYSIS DI PT. PLN (PERSERO) RAYON DAYA MAKASSAR - Rizal A Duyo (Fakultas Teknik Universitas Muhammadiyah Makassar, 2020)
Distribution network is part of power network closest to society, distribution network is grouped into two namely: primary and secondary distribution network. The primary distribution voltage used by pln is 20 kv, 12 kv and 6 kv. The primary distribution voltage which tends to be developed by pln is 20 kv. This study aims To determine the main cause of disturbance in power distribution network at Rayon Daya Makassar using FTA (Fault Tree Analisys). The results of this study can be seen from the considerable difference between the electrical energy delivered from the substation with the electrical energy generated from customer consumption. The cause of the interference is: JTM component (I1) of 55 disruptions (12.5%), JTM equipment (I2) of 30 disruptions (6.7%), disturbances Transformer (I3) as many as 8 interruptions (1.8%) , natural disturbance (I4) as much as 1 interference (0,2%), external disturbance (E1) counted 15 disturbance (3%), natural disaster (E2) counted 61 disturbance (13,7%), work of other party / E3) as many as 15 disruptions (0.33%), kites, banners or due to faulty electrical distribution network installation (E4) as many as 258 interruptions (58.2%). After conducting research on the causes of disruption of power distribution network at UPJ Rayon Daya Makassar and analyzed using Fault Tree Analyzes (FTA) it is known that the main cause of disturbance is human disturbance, in the form of playing kites, banners, and excavation of PDAM channel. It can be seen that during May 2016 until January 2017 there were 308 disruptions.